Suicide in doctors: a study of risk according to gender, seniority and specialty in medical practitioners in England and Wales, 1979–1995. Issue 5 (1st May 2001) - Hawton, K; Clements, A; Sakarovitch, C; Simkin, S; Deeks, J J
Abstract : STUDY OBJECTIVE: To investigate the suicide risk of doctors in England and Wales, according to gender, seniority and specialty. DESIGN: Retrospective cohort study. Suicide rates calculated by gender, age, specialty, seniority and time period. Standardised mortality ratios calculated for suicide (1991–1995), adjusted for age and sex. SETTING: England and Wales. SUBJECTS: Doctors in the National Health Service who died by suicide between 1979 and 1995, identified by death certificates. Population at risk based on Department of Health manpower data. MAIN RESULTS: Two hundred and twenty three medical practitioners in the National Health Service who died by suicide or undetermined cause were identified. The annual suicide rates in male and female doctors were 19.2 and 18.8 per 100 000 respectively. The suicide rate in female doctors was higher than in the general population (SMR 201.8; 95% CI 99.7, 303.9), whereas the rate in male doctors was less than that of the general population (SMR 66.8; 95% CI 46.6, 87.0). The difference between the mortality ratios of the female and male doctors was statistically significant (p=0.01), although the absolute suicide risk was similar in the two genders. There were significant differences between specialties (p=0.0001), with anaesthetists, community health doctors, general practitioners and psychiatrists having significantly increased rates compared with doctors in general hospital medicine. There were no differences with regard to seniority and time period. CONCLUSIONS: There is an increased risk of suicide in female doctors, but male doctors seem to be at less risk than men in the general population. The excess risk of suicide in female doctors highlights the need to tackle stress and mental health problems in doctors more effectively. The risk requires particular monitoring in the light of the very large increase in the numbers of women entering medicine.